The Investigation of Rayleigh-Taylor Mixing with a Premixed Layer by BHR Turbulence Model (Advances in Applied Mathematics and Mechanics, 2022)
The Rayleigh-Taylor mixing with a premixed layer is investigated in thepresent study. A BHR-II turbulence model is employed to simulate the Rayleigh-Taylormixing with different premixed layers. The implementation of the BHR-II model is described in detail and validated in canonical problems. Afterwards, the classic Rayleigh-Taylor instability (RTI) with a premixed layer is studied. Effects of density ratio, layerthickness and density profiles on the late time behaviour of classic RTI are analysed,and the results are also compared with ILES data. It turns out that the premixed layerdelays the transition time of turbulent mixing. The late time behaviours of differentpremixed cases show a similar trend with the similarity of their distributions of turbulent kinetic energy. It is also shown that the premixed layer has little effect on thetilted angle in the canonical tilted rig case while the temporal evolution of the turbulentmixing at the early beginning is distinctly influenced by the premixed layer.